2017
DOI: 10.1080/15592324.2017.1414122
|View full text |Cite
|
Sign up to set email alerts
|

Further insights into the role of NIN-LIKE PROTEIN 7 (NLP7) in root cap cell release

Abstract: The root cap protects the root from environmental stress and senses gravity. Cells of the last layer of the root cap are shed in a developmentally programmed process. We previously showed that the transcription factor NIN-LIKE PROTEIN7 (NLP7) regulates root cap cell release likely through regulation of CELLULASE5 (CEL5). Here we provide a supplement to that work. We hypothesized that the nlp7 mutant has defects in additional root cap functions. We find that neither gravity sensing nor expression of a root cap … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
(35 reference statements)
0
1
0
Order By: Relevance
“…Recently, it is reported that in A. thaliana NLPs also take a role in developmentally programmed processes independent of nitrate. AtNLP7 can regulate root cap cell release likely through regulation of CELLULASE5 (Karve and Iyer-Pascuzzi 2018). So further studies are clearly required to understand how OsNLP4 reacts to nitrate signaling with changing from inactive form to active one and the functions of other OsNLPs in rice.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it is reported that in A. thaliana NLPs also take a role in developmentally programmed processes independent of nitrate. AtNLP7 can regulate root cap cell release likely through regulation of CELLULASE5 (Karve and Iyer-Pascuzzi 2018). So further studies are clearly required to understand how OsNLP4 reacts to nitrate signaling with changing from inactive form to active one and the functions of other OsNLPs in rice.…”
Section: Discussionmentioning
confidence: 99%